Features of Cell-Mediated Immunity in Children with Congenital Ichthyosis and Their Role in the Pathogenetic Management - Karine O. Avetisyan; Nikolay N. Murashkin; Svetlana G. Makarova; Svetlana S. Petrichuk; Daria G. Kuptsova ("Paediatrician" Publishers LLC, 2023)
Background. Congenital ichthyoses (CIs) are a heterogeneous clinical-etiological group of genodermatoses. Typical clinical symptoms of this disease, regardless of the form, are generalized erythroderma, peeling, itching, hyperkeratosis, severe structural and functional disorders of the epidermal barrier, other organs and systems. Patients have an extremely low quality of life due to changes in appearance, discomfort, constant disease symptoms. Thus far, there are no effective treatment methods for ichthyosis. That is why scientific search for new therapies is the topical issue in pediatrics and pediatric dermatology.Objective. The aim of the study is to examine the cell-mediated immunity state in patients with CI via assessment of the pattern of lymphocyte subpopulations in peripheral blood. The research was conducted to study the content of the main and small lymphocyte subpopulations in 86 patients with established diagnosis of CI aged from 1 month to 18 years. The diagnosis was made according to the clinical data and the results of molecular genetic testing. Comparative analysis of blood immunological indicators in children with CI and in patients with other immunemediated chronic dermatoses: atopic dermatitis (AD; n = 68) and psoriasis vulgaris (n = 55).Methods. The level of T lymphocytes, T helpers (Th), cytotoxic T lymphocytes (Tc), B lymphocytes, NK cells, Treg-cells (Treg), activated T helpers (Thact), Th17 lymphocytes in peripheral blood was evaluated via flow cytometry using monoclonal antibodies. Statistical analysis was performed via Statistica 10.0. Differences between the groups were assessed via Mann-Whitney non-parametric test, differences were considered significant at p < 0.05.Results. A significant increase of activated T-helpers level in peripheral blood was revealed in patients with CI and psoriasis compared to children with AD (p < 0.001), as well as an increased levels of B-lymphocytes and Treg in children with CI (p < 0.05).Conclusion. Children with CI have shown some features of cell-mediated immunity such as: pathological activation of Th lymphocytes, impaired terminal differentiation of naive CD4+ cells to Thact, Treg, Th17 lymphocytes and their proliferation. Comparative analysis of mentioned immunological indicators in children with CI, psoriasis and AD has shown comparable results of increased Thact lymphocytes levels in patients in CI and psoriasis groups. This results open up potential of using immunobiological drugs of psoriasis target therapy within the new management strategy for children with CI.